Understanding sports massage - Benjamin, Patricia J. 1947-; Lamp, Scott P. 1956- (Human Kinetics, 2005)
The book illustrates and explains massage techniques in detail and describes the procedures involved in conducting effective sports massage sessions, including determining goals, organizing the session, and choosing and applying techniques." "Understanding Sports Massage, Second Edition, also features many updates and improvements from the first edition